Work organization and mental health of workers dealing with organ and tissue donation for transplants - Bernardes, Ana Rita Barreto; Menezes, Lucianne Sant'Anna de (Ciência & saude coletiva, 2021)
This paper presents the main results of a study developed in a Graduate Program from 2016 to 2018 with all workers from the Intra-Hospital Commission for Donating Organs and Tissues for Transplants of a Public Tertiary Hospital, in which the general proposal was to analyze the organization and the work process of this team, investigating mental strain in the workers involved. This qualitative exploratory research in Occupational Health focused on Work-Related Mental Health. The material selected for the study was retrieved by bibliographic survey, participant observation, social questionnaire, and semi-directed individual interview. It was subjected to thematic content analysis and referred to the theoretical category of mental strain. The organization and work process analysis evidenced that workers are subject to biomechanical, biological, and mental health accident risks. This condition characterizes the wear process of these workers, in particular the mental strain, which can lead to health loss. Nevertheless, workers are emotionally connected to work, which can be a source of sublimation, providing pleasure and satisfaction.